EFFECT OF CRUDR AND EXTRACT OF PROPPOLES AS ADDITIVES ON IMMUNOLOGICAL AND BIOCHEMICAL ON CYPRINUS CARPIO CHALLENGED WITH AEROMONAS HYDROPHILA - Maymounah. A. Al-Gburi; S. A. Mustafa (The Iraqi Journal of Agricultural science, 2025)
The present study was carried out to investigate the effect of propolis [(crud propolis and Water Ethanol Extract Propolis (WEEP)] as feed additive on biochemical and immunological in common carp Cyprinus carpio challenged with Aeromonas hydrophila. A total of 60 C. carpio, (75±10g) were randomly stocked into five treated groups in duplicate as follows: control group (C) fish were fed basal diet without any addition of propolis; T1 fish were fed basal diet supplemented with 10g/kg crud propolis; T2, T3 and T4 fish were fed WEEP at concentrations of 2g, 4g and 8 g/kg diet.Results indicated that The highest albumin content was found in T1 which showed a significant increase (P≤0.5) compared to C+ group, and globulin content did not show significant differences between T1, T2, T3, T4, C- and C+ groups. Cholesterol level did not lead to changes in all (P > 0.05) treated groups (T1, T2, T3 and T4) when compared with the control group. The glucose level showed a significant (P≤0.05) increase in all WEEP groups (T2, T3, and T4). The highest weighted Somatic Spleen Index (SSI) was reported in T3 which showed a significant (p < 0.05) increase compared to T1. The result of nitro blue tetrazolium (NBT) assay showed non-significant differences (P > 0.5) in T1, T2, T3 and T4 compared to C and C+ groups.